Analisis Model Pembelajaran Sentra Dalam Meningkatkan Minat Bakat Pada Anak Usia Dini - Tadzkirah; Putri Annisa (STAI Al-Amin Gersik Kediri Lombok Barat NTB, 2024)
Early childhood education is education aimed at enabling the child's full growth and development. However, in principle, the educational process is not only carried out to convey the limits of knowledge. The early childhood learning process is an interaction between teachers, friends, or other adults in an environment to achieve their developmental tasks. The central learning model is a child-centered learning approach and learning is carried out in circles (Circle Time) and play centers. The aim of this research is to analyze the central learning model in increasing interest and talent in class B3 children at TKIT Al-Azizi Parepare. The research method used is a descriptive qualitative method. The results of the research show that the process of implementing central learning in class B3 at TKIT Al-Azizi Parepare can increase children's interest and talents depending on the class presentation provided by the teacher. There are 4 types of learning center models that take place at TKIT Al-Azizi including science centers, arts centers, preparation centers and block centers. From the four existing center models, teachers can find out where children's interests and talents are more prominent.